Pengaruh Fraksi Ukuran dan pH Pada Flotasi Mineral Sulfida - Subandrio Subandrio; Christin Palit; Irfan Marwanza; Emmy Fatmi B. I.; Muhammad Idris Juradi (Jurnal Geomine, 2022)
The ore used in this study is galena ore (PbS) which is a type of sulfide mineral. In this experiment, several variations of important variables were carried out. The variables that were varied namely: feed size fraction with a range of 140 - 325 mesh (105 - 44 microns), pulp pH between 7 – 11, and retention time between 3 - 8 minutes. The experimental results show that the smaller the feed size, the Pb content (%) tends to increase, For the pH of the pulp, the best Pb content was at pH 9.5. The higher the pH the bubbles formed tended to be stable so that the material was perfectly lifted to the surface. The best flotation time was obtained at 6.5 minutes. Retention time greatly affects the effectiveness of the reagents used in the flotation process. Best on experiments, The best condition is at the size of -200 + 230 mesh, pH of the pulp 9,5 with retention time 6,5 minutes with a Pb content of 27%.